Legal Review of Online Fraud Linked to Criminal Liability Aspects (Case Study: Decision Number 372/Pid.B/2020/PNSby) - Asheka Malikus Zachwa; Labib Muttaqin (Universitas Muhammadiyah Surakarta, 2025)
The rapid development of information technology has negative impacts, for example, online fraud carried out in various modes. Existing regulations have not been able to bridge the law enforcement of online fraud crimes if they are not balanced by law enforcement factors, so it is important to know a judge's legal considerations on the related crime whether it is in accordance with the regulations and the realization of legal certainty. Normative legal research methods with a descriptive approach, with secondary data including primary, secondary, and tertiary legal materials. Literature study data collection techniques, which are then analyzed qualitatively. The study aims to determine the legal certainty in Decision Number 372 / Pid.B / 2020 / PN Sby. The results of the study show that Decision Number 372 / Pid.B / 2020 / PN Sby is in accordance with the legislation and realizes legal certainty.